2022
DOI: 10.1007/s40259-022-00533-x
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Evaluation of Biosimilars: Refinement of Principles Based on the Scientific Evidence and Clinical Experience

Abstract: The World Health Organization (WHO) guidelines on evaluation of similar biotherapeutic products (SBPs; also called biosimilars) were adopted by the WHO Expert Committee on Biological Standardization (ECBS) in 2009. In 2019, the ECBS considered that a more tailored and potentially reduced clinical data package may be acceptable in cases where this was clearly supported by the available scientific evidence. The goal of this publication is to review the current clinical experience and scientific evidence and to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 69 publications
0
27
0
Order By: Relevance
“…Indeed, it would not be practical to mandate such studies, and if such studies were conducted the sheer number of studies would strain regulatory resources. Further considering the value of randomized clinical trials in the development of biosimilars, evidence has accumulated that phase 3-style efficacy and safety studies rarely contribute pivotal data to the totality of data supporting initial approval [54][55][56]. Likewise, analysis of the data from the studies identified in this systematic review clearly reveals that meaningful data on biosimilar-to-biosimilar switching can be obtained without the need for RCTs.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, it would not be practical to mandate such studies, and if such studies were conducted the sheer number of studies would strain regulatory resources. Further considering the value of randomized clinical trials in the development of biosimilars, evidence has accumulated that phase 3-style efficacy and safety studies rarely contribute pivotal data to the totality of data supporting initial approval [54][55][56]. Likewise, analysis of the data from the studies identified in this systematic review clearly reveals that meaningful data on biosimilar-to-biosimilar switching can be obtained without the need for RCTs.…”
Section: Discussionmentioning
confidence: 93%
“…This provided an opportunity to evaluate new developments, identify areas where the guidance could be more flexible without compromising the basic principles, and allow for the provision of additional explanation of the possibility of reducing the amount of data needed for regulatory approval. 6,7 The use of state-of-the-art methodologies in the characterization and in vitro functional testing of biosimilars and the understanding of quality attributes that may impact clinical performance provide the potential to reduce the clinical data requirements in biosimilar assessment. In response to the recommendation, work to revise the guidelines was initiated, and the final draft revision after extensive consultation involving several rounds of regulatory expert review and two rounds of public consultation was adopted by the WHO ECBS in April 2022.…”
Section: Safety and Efficacy Of Biological Products Throughout Their ...mentioning
confidence: 99%
“…The next important factor is the complex regulatory environment and ethical issues, including intellectual property rights, cell/tissue banking, sample transfer regulations, toxicology (safety issues), product manufacturing regulations, approval process for the product before hitting the market, clinical trials, etc. [ 74 ].…”
Section: Healthcare Scenario Translational Research—initiatives Prosp...mentioning
confidence: 99%